(untitled) (Marketing Journal, 2026)
Abstract This article analyzes the current issues of developing logistics services in manufacturing enterprises based on a systemic approach. The study scientifically substantiates the changes in the role and functional content of logistics in the context of the evolution of production systems, industrial revolutions, and the digital economy. Particular attention is paid to ensuring the integrity of the production and logistics environment, synchronizing material and information flows, optimizing inventories, and reducing logistics costs. Furthermore, the priority directions for the effective organization of logistics services in enterprises are justified, including the implementation of digital technologies, the application of lean production principles, strengthening integration among supply chain participants, and the formation of a process-oriented management system. Keywords: production logistics, production-logistics system, supply logistics, distribution logistics, resource movement logistics, transport logistics, internal production flows, warehousing, digital platforms, automated control systems.